Penguatan Moderasi Beragama melalui Nilai-nilai Al-Qur’an dalam Tradisi Wungon di Pemalang - Safitri, Hani Hasnah; Khumaedy, Agus; Ta'rifin, Ahmad; Albab, Ulul (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2024)
Indonesia has the advantage of being a peaceful and prosperous country with diverse religions and cultural traditions. This research aims to examine tolerance and harmony in the "Wungon" tradition by implementing the values of religious moderation based on the Koran. By using field research methods and a qualitative descriptive approach, this research shows that: 1) The Wungon tradition can strengthen the values of religious moderation in the younger generation as a form of tolerance and harmony between religious communities. 2) The Wungon tradition applies four main indicators of successful religious moderation compiled by the Ministry of Religion, Republic of Indonesia. First, the Wungon tradition plays a role in strengthening nationalism which is reflected through national songs with the theme of love for the homeland which residents sing as the implementation of QS Al-Qashash: 85. Second, tolerance in the Wungon tradition is seen through interactions between Muslims and non-Muslims in maintaining friendship and respecting each other's differences by exchanging food and giving to each other as an actualization of the QS. Al-Mumlahanah: 8. Third, the politeness and gentleness of the citizens are manifestations of anti-violence education as an implementation of QS. Ali-Imran: 159. Fourth, integration of QS. Al'A'raf: 199 represents the friendly attitude and acceptance of Pemalang residents towards the Wungon tradition which does not conflict with religious teachings. This research contributes to finding the concept of strengthening the values of religious moderation based on local wisdom. Apart from that, this research can also be used as a basis for integrating cultural practices as a home for religious moderation.